Perancangan Sistem Website Untuk Pemesanan Makanan dan Minuman Menggunakan QR Code Demi Tercapainya Kepuasan Konsumen Pada Sekawan Kopi & Space - Wirati, Triantya Wahyu; Puspitasari, Tiara Suci; Muhammad Farouq Dhyaulhaq, Muhammad Farouq (Coopetition : Jurnal Ilmiah Manajemen, 2024)
A coffee shop or coffee shop is one of the contemporary business places that is in great demand from young people to adults. In the Antapani area there is a coffee shop called Sekawan Kopi & Space which is a new coffee shop business that opened in 2023 and still uses conventional methods to carry out its business processes. After analyzing the current business processes, several obstacles were found, such as the ordering system which was still done manually, resulting in less efficient service. Where queues often occur, orders pile up and orders take a long time, incorrect order input and so on. Therefore, this project aims to design a site menu that can help overcome these problems and increase customer satisfaction with faster and easier service efficiency. The methods used in this project include literature study, direct observation, interviews with related parties, and in-depth analysis of the business processes being carried out. The result of this project is designing the Sekawan Kopi & Space website menu using Qr Code.